BALToma masquerading as pulmonary tuberculosis. (14th November 2014) - Magazine, Rahul; Shahul, Hameed Aboobackar; Monappa, Vidya; Chogtu, Bharti
Abstract : A 53-year-old man with a significant smoking history presented with chronic cough, exertional breathlessness, intermittent fever, weight loss and anorexia. A review of his past medical records revealed he was diagnosed to have sputum smear-positive pulmonary tuberculosis 5 years earlier, for which he had received multiple courses of incomplete antitubercular therapy. This time, though he was primarily suspected to have active pulmonary tuberculosis, lack of microbiological evidence and further investigations including histopathological evaluation of lung lesions confirmed a diagnosis of Marginal zone B cell lymphoma of mucosa-associated lymphoid tissue (MALToma/BALToma). The patient was managed with radical radiation therapy to which he responded well.